Effectiveness of photodynamic therapy on Candida species isolated from oral samples of children exposed and not exposed to HIV - Silva, Francine Cristina Da; Rosa, Luciano Pereira; Pinheiro, Antonio Luiz Barbosa; Koga-ito, Cristiane Yumi; AraÚjo, Bruno Pereira De; Viana, Vivian De Oliveira; Campos, Laíze Aparecida Nunes Lopes (Faculdade São Leopoldo Mandic, 2016)
ABSTRACTObjective: Identify yeast species isolated from unexposed, exposed and HIV-carrier children, and verify the effectiveness of low power laser photodynamic therapy (PDT) on the yeasts species belonging to the Candida genus.Methods: Fifty children assisted by the Public Health Program of the city of Vitória da Conquista, Bahia, were selected and divided into three groups: unexposed to HIV, exposed to HIV during pregnancy, and HIV-carrier. Saliva samples were collected in a disposable sterile universal container and were plated to Sabouraud dextrose agar supplemented with 0.1 mg/mL chloramphenicol. The plates were incubated at 37°C for 48 h. Three strains of each patient were identified by using an API 20 C AUX system. The strains were submitted to photodynamic therapy (PDT) with a 660 nm low power laser and methylene blue dye at different times of irradiation (90, 180 and 282 sec.).Results: The results showed that the most prevalent species was Candida albicans followed by Candida famata (second most prevalent in unexposed to HIV and HIV carriers)) and Candida parapsilosis (second most prevalent in exposed to HIV group). The CFU/mL of Candida spp. decreased significantly (p<0,05) in all groups treated with PDT compared to the controls. Photodynamic therapy treatments at different exposure times (e.g., PS+L90+, PS+L180+, PS+L282+) revealed that the exposure time of 282 sec. gave the highest reduction of the mean logarithmic CFU/mL.Conclusion: Candida albicans was the most prevalent Candida species in these three groups and Candida non-albicans species, when combined, amounted to a significant percentage of Candida isolates. Photodynamic therapy was effective in inactivating the Candida spp. isolated from the oral cavity of children not exposed to HIV, exposed to HIV and HIV-carriers, with the best photodynamic therapy irradiation time being 282 sec.

RESUMOObjetivo: Identificar espécies de leveduras isoladas de crianças não expostas, expostas ao HIV e portadoras de AIDS, e verificar a eficácia da terapia fotodinâmica com laser de baixa potência sobre as espécies de leveduras pertencentes ao gênero Candida.Métodos: Cinquenta crianças atendidas pelo Programa de Saúde Pública da cidade de Vitória da Conquista, Bahia, foram selecionadas e divididas em três grupos: não expostas ao HIV, expostas ao HIV durante a gravidez e portadoras da AIDS. Amostras de saliva foram coletadas em um recipiente universal descartável estéril e foram semeadas em ágar Sabouraud dextrose suplementado com 0,1 mg / mL de cloranfenicol. As placas foram incubadas a 37°C durante 48h. Três cepas de cada paciente foram identificadas utilizando o sistema API 20 C AUX. As cepas foram submetidas à Terapia Fotodinâmica com laser de baixa potência de 660 nm e corante azul de metileno em diferentes tempos de irradiação (90, 180 e 282 segundos).Resultados: Os resultados mostraram que a espécie isolada mais prevalente nos grupos estuddos foi Candida albicans, seguida de Candida famata (segunda mais prevalene nos grupos não expostos ao HIV e com AIDS) e Candida parapsilosis (segunda mais prevalente no grupo exposto ao HIV). Houve diminuição significante de CFU/ml de Candida spp. (p <0,05) em todos os grupos tratados com terapia fotodinâmica, em comparação com os controles. A terapia fotodinâmica, nos diferentes tempos (e.g., PS+L90+, PS+L180+, PS+L282+) mostrou que o tempo de 282 seg. apresentou a maior redução em media de logarítmo de UFC/mL.Conclusão: Candida albicans foi a espécie de Candida mais prevalente isolada nos três grupos e as espécies de Candida não-albicans, quando combinadas, contribuíram com porcentagem significativa dos isolados de Candida. A PDT foi eficaz na inativação de Candida spp. isoladas a partir da cavidade oral de crianças não expostas, expostas ao HIV e portadoras da AIDS, com o melhor tempo de irradiação sendo o de 282 seg.
Efetividade da terapia fotodinâmica sobre espécies de Candida isoladas de amostras bucais de crianças expostas e não expostas ao HIV
Keywords: Candida; Children; HIV; Methylene blue; Photochemotherapy; Candida; Criança; HIV; Azul de metileno; Fotoquimioterapia